1988
DOI: 10.1007/bf00140262
|View full text |Cite
|
Sign up to set email alerts
|

Paleoclimatic variability at frequencies ranging from 1 cycle per 10 000 years to 1 cycle per 1000 years: Evidence for nonlinear behaviour of the climate system

Abstract: The paleoclimatic variability at frequencies ranging from 10 -4 cycle per year (cpy) to 10 -3 cpy is investigated using a set of three deep-sea cores from the Indian Ocean. Three frequency bands of high paleoclimatic variability are first defined using upper and lower limits of the significant spectral power concentrations: the bands are centered around the spectral maxima located at 10.3, 4.7, and 2.5 kyr. The localisation of spectral lines is then refined by highresolution spectral analysis.Some of the resul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
45
0
1

Year Published

1998
1998
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 40 publications
6
45
0
1
Order By: Relevance
“…The study of the δ 18 O concentration in ice core (Dansgaard et al, 1984) showed a ∼ 2500-year climatic cycle to exist. A ∼ 2400-year quasiperiod was observed in the δ 18 O concentration of deep see core with high sedimentation rates (Pestiaux et al, 1988). Similar periodic behaviour has been found in GRIP2 and GISP ice cores over the last 12 000 years.…”
Section: Palaeoclimatology Datasupporting
confidence: 75%
See 1 more Smart Citation
“…The study of the δ 18 O concentration in ice core (Dansgaard et al, 1984) showed a ∼ 2500-year climatic cycle to exist. A ∼ 2400-year quasiperiod was observed in the δ 18 O concentration of deep see core with high sedimentation rates (Pestiaux et al, 1988). Similar periodic behaviour has been found in GRIP2 and GISP ice cores over the last 12 000 years.…”
Section: Palaeoclimatology Datasupporting
confidence: 75%
“…The existence of a ∼ 2400-year cycle is proved in a number of studies of climatic data, (see e.g. Dansgaard et al, 1984;Pestiaux et al, 1988;Röthlisberger, 1986;Arabadzi, 1986;Levina and Orlova, 1993;O'Brien et al, 1995). This evidence of long-term change of climate allows us to assume that the variation of the 14 C concentration with ∼ 2400-year period has a climatic origin (Damon and Sonett, 1992).…”
Section: The Nature Of ∼ 2400-year Modulationmentioning
confidence: 92%
“…These subMilankovitch signals are recorded in both marine and terrestrial data from different parts of the world, i.e. at high latitudes in the Atlantic Ocean (Hagelberg et al, 1994), in Spain (Rodríguez-Tovar and Pardo-Igúzquiza, 2003), in the Correspondence to: E. Tuenter (tuenter@knmi.nl) Mediterranean Sea (Larrasoaña et al, 2003;Steenbrink et al, 2003;Becker et al, 2005), in the equatorial Pacific Ocean (Hagelberg et al, 1994), in marine sediments influenced by the strength of the African monsoon (Pokras and Mix, 1987;Hagelberg et al, 1994;McIntyre and Molfino, 1996) and by the strength of the Asian monsoon (Pestiaux et al, 1988;Naidu, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…Focus is on the African and Asian monsoon at Northern Hemisphere low latitudes, as most sediment records showing sub-Milankovitch variability seem to be influenced by the strength of the monsoon (Pokras and Mix, 1987;Pestiaux et al, 1988;Hagelberg et al, 1994;McIntyre and Molfino, 1996;Larrasoaña et al, 2003). Sub-Milankovitch signals at Northern Hemisphere high and mid-latitudes will also be briefly described.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, Pestiaux, Duplessy and Berger (1987), after an analysis of four deep-sea cores from the Indian Ocean that is influenced by the monsoon circulation, estimate significant spectral maxima located at 10.2 +/-1.2, 4.6 +/-0.3 and 2.3+/-0.2 Kyr, roughly including harmonics of themselves and of the 41, 23 and 19 Kyr periodicities found in insolation (Berger and 30 Pestiaux, 1984). However, when we select only the two cores of the Indian Ocean NE corner, more isolated from the Southern Earth Syst.…”
Section: The Resonant Environment Of the Earth's Climate Systemmentioning
confidence: 99%